2018
DOI: 10.1177/0748233718760419
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine affects craniofacial chondrogenesis and axial skeleton mineralization in zebrafish (Danio rerio)

Abstract: Atrazine is a commonly used herbicide that has previously been implicated as an endocrine-disrupting compound. Previous studies have shown that estrogenic endocrine-disrupting compounds affect the development of the heart, cartilage, and bone in zebrafish ( Danio rerio). To determine whether atrazine has effects similar to other endocrine disruptors, zebrafish embryos were treated with a range of atrazine concentrations. Atrazine treatment at a low concentration of 0.1 µM resulted in significant differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…The hatching delays observed are in accordance with previous reports using the isolated atrazine pure principle at lower concentrations ( Liu et al, 2016 ; Walker et al, 2018 ). The interrelation between survival and hatching rates may hinder some deleterious effects that are not evident in the later parameter, as the lack of hatching delay in 5.0 mg/L atrazine-exposed animals only includes the surviving half population and may be considered when interpreting data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The hatching delays observed are in accordance with previous reports using the isolated atrazine pure principle at lower concentrations ( Liu et al, 2016 ; Walker et al, 2018 ). The interrelation between survival and hatching rates may hinder some deleterious effects that are not evident in the later parameter, as the lack of hatching delay in 5.0 mg/L atrazine-exposed animals only includes the surviving half population and may be considered when interpreting data.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings agree with Velki et al (2017) , that found 96 h-LC50 values of 6.31 ± 0.19 mg/L for zebrafish embryos exposed to diuron non-commercial formulation on the FET assay. Walker et al (2018) , also using isolated atrazine, found atrazine-induced mortality in an equivalent time window, but at lower concentrations.…”
Section: Discussionmentioning
confidence: 91%
“…The main effects of ATZ on biology are toxic effects and endocrine interference. According to the research by Benjamin [11], ATZ can cause stunted vertebrae development of zebra fish, and excessive ATZ (more than 3 mmol/L) can cause serious defects in the craniofacial development of zebrafish. The research conducted by HAYES [12] and others found that, when the growth of the African tree frog from larva to adult are exposed to the ATZ solution with the concentration of 0.1 μg/L, 20% of the young frogs will develop into hermaphrodites, which indicates that ATZ with a low concentration can feminize the male African tree frog.…”
Section: Introductionmentioning
confidence: 99%
“…There were no effects on apical endpoints such as mortality, hatching rate, or gross malformations so the relevance of these responses is questionable. Significant changes in heart rate and development of craniofacial cartilage in embryos of D. rerio have been reported (Walker et al 2018). Heart rate was significantly increased at unrealistic concentrations !216 mg atrazine/L at 72-and 96 h post fertilization.…”
Section: Physiological and Biochemical Effects In Vivomentioning
confidence: 98%
“…Wirbisky et al (2016c) reported no change in hatching success of zebrafish embryos from adult zebrafish that were previously exposed to atrazine at 0, 0.3, 3, and 30 mg/L from 1 through 72 h post fertilization. Adverse effects on hatching of zebrafish was reported only at a concentration of 1078 mg atrazine/L and not below (Walker et al 2018). A study on the effects of formulated atrazine on hatching and successful emergence of sockeye salmon (Oncorhynchus nerka) from gravel showed no effects on these endpoints at concentrations up to 250 mg/L (Du Gas et al 2017).…”
Section: Hatching Of Eggs In Fish and Amphibiansmentioning
confidence: 99%